The Russian capitalists - Ewald, R. (Swimming World and Junior Swimmer, 1994)
About the main ideas of training conception of Viktor Avdienko (Russian "Coach of the year" in 1992 and 1993). As far as Avdienko's own training methods, he thinks it's more important to build coordination between muscles to develop force than lift weights purely to increase strength. He says his team does more repetitions with lighter weights than U.S. swimmers. "We have some considerable differences (from the U.S.) in the concept of preparation for championships," he said. "In dryland training when working on power abilities, we don't use an overwhelming amount of weight. And in the water, it is necessary to train the swimmer for competition. The swimmer doesn't have to work to the limit in training. He just has to accumulate the buildup of his resources. You do not want to wear the swimmer out."